A Case of Suspected Cardiac Amyloidosis: A Diagnostic Challenge in a 22-Year-Old Male with Restrictive Cardiomyopathy - I Gusti Ayu Aruna Krisnadewani; Bayu Setia (International Medical Journal Corp. Ltd, 2026)
Introduction Cardiac amyloidosis (CA) is a progressive and often terminal infiltrative cardiomyopathy resulting from the extracellular deposition of misfolded protein fibrils—primarily immunoglobulin light chains (AL) or transthyretin (ATTR)—within the heart muscle. While historically perceived as a rare condition affecting the elderly, advances in non-invasive imaging have revealed CA as an underdiagnosed cause of heart failure. However, its manifestation in young adults remains exceptionally rare, presenting a significant diagnostic challenge for general practitioners. Early recognition is vital, as subtype-specific therapies can significantly alter the clinical trajectory. Case Illustration We report the case of a 22-year-old male who presented with a two-week history of progressive dyspnea, orthopnea, abdominal distention, and periorbital edema. Physical examination revealed signs of systemic congestion, including ascites (shifting dullness) and decreased breath sounds in the right lung, alongside a blood pressure of 130/90 mmHg and a heart rate of 94 bpm . Laboratory findings were remarkable for a severely elevated NT-proBNP of 8177.11 pg/mL and a high hemoglobin of 18.2 g/dL . Chest radiography demonstrated cardiomegaly (CTR 63%), pulmonary edema, and bilateral pleural effusion. Electrocardiography (ECG) revealed low-voltage QRS complexes, which stood in stark contrast to the echocardiographic evidence of significant ventricular wall thickening (IV S 1.27 cm, LV PW 1.83 cm, ) and a reduced ejection fraction of 35.3% . The discordance between ECG voltage and echocardiographic mass, combined with Grade III diastolic dysfunction, strongly suggested cardiac amyloidosis. Discussion The diagnostic hallmark in this case is the